12 July 2006

1 = 2

a = b
a^2 = ab
a^2 - b^2 = ab - b^2
(a+b)(a-b) = b(a-b)
(a+b) = b
2b = b
Therefore...
2 = 1

Prove me wrong

12 comments:

~*Joyzey*~ said...

Show off! j/k

Grasshopper said...
This comment has been removed by a blog administrator.
Grasshopper said...

if at a=b, then a-b=0. Therefore, to get from

(a+b)(a-b) = b(a-b)

to

(a+b) = b

You have to divide both sides by (a-b), which equals zero, which isn't possible. That's the flaw.

TheEarthCanBeMoved said...

yup

Palm boy said...

Schooled...

And the earth can be moved.

~*Joyzey*~ said...

slacking off with the updates again?

Anonymous said...

Remember, he is doing summer school. Jason is probably busy studying (which is what he should be doing).

~*Joyzey*~ said...

*puts head down* Sorry Mrs. Koller.

Malorie said...

Yes... I do, but at the same time... Gerry has been got either, so I think I'm safe.

TheEarthCanBeMoved said...

Actually,
He got a copy of HALO.
And that's been taking all his time.

j/k
;-)

Anonymous said...

I hope you're kidding.

мαdd said...

My mad Freshman equasion skills can't add up to your mad Awesome Marine Corps Owing Me At Every Level skills.